Pengaruh Tingkat Pendidikan Orang Tua terhadap Motivasi Belajar Siswa di SMK Unggulan NU Mojoagung Jombang - Eko Hadi Wardoyo (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
This study aims to find the effect of parents' educational level on student learning motivation in the SMK Unggulan NU Mojoagung Jombang. This type of research is quantitative descriptive, with data collection techniques of observation, interviews, questionnaires and documentation. The data analysis technique uses the product moment correlation analysis technique. The results showed that based on the calculated<rtable both at the significance of 5% (0.017<0.3961) and 1% (0.017<0.5052). Based on the author's analysis, it can be seen that there is no significant effect of parents' educational level on student learning motivation in the SMK Unggulan NU Mojoagung Jombang..